Radiological approach to multinodular and vacuolating neuronal tumor: Two case report: Radiological approach to MVNT: Two case report - Ocak Karataş, Şükrüye Firuze; Beyhan, Murat; Gökçe, Erkan (Journal of Surgery and Medicine, 2023)
Multinodular and vacuolating neuronal tumors (MVNT) are indolent, low-grade, superficial neuronal tumors of the cerebrum that consist only of neuronal cells in adults. They were first reported in 2013 by Huse et al. and defined by the World Health Organization in 2016. MVNT is characterized by vacuolated tumor nodules with glial and/or neuronal differentiation histopathologically. MVNT is most commonly located in the temporal lobe. Radiologically, it has a subcortical, soap-bubble morphology, sometimes extending to the cortex, and is almost as hyperintense as cerebrospinal fluid on T2-weighted images. Its signal is not suppressed on the FLAIR sequence, and there is no diffusion restriction on diffusion-weighted images. Usually, there is no enhancement after gadolinium injections, but a few reports show weak enhancement in the literature. In the first case, we present a 22-year-old female with MVNT who underwent MRI for a complaint of dizziness which was detected incidentally. MRI showed a clustered multinodular lesion in the left superior frontal gyrus that was hyperintense on T2-weighted/FLAIR series and isointense with gray matter on T1-weighted images. There was no diffusion restriction or contrast enhancement on MRI. In the second case, a 51-year-old female with complaints of numbness and pain in her left arm had an MRI that showed a lesion in the right cerebral hemisphere at the temporoparietal junction. The lesion did not cause edema or mass effect and was distributed in the cortical-subcortical area. The lesion was hyperintense in T2-weighted and FLAIR series and consisted of many millimetric nodular components in close intensity with gray matter in the T1-weighted series. No contrast enhancement was detected. Knowing the characteristic imaging findings of MVNT is important in avoiding aggressive diagnosis and treatment approaches in asymptomatic cases. In conclusion, MVNT is a newly identified tumor that appears hyperintense on the FLAIR sequence and should not be operated on.